Aesculetin Inhibits Airway Thickening and Mucus Overproduction Induced by Urban Particulate Matter through Blocking Inflammation and Oxidative Stress Involving TLR4 and EGFR - Su-Yeon Oh; Yun-Ho Kim; Min-Kyung Kang; Eun-Jung Lee; Dong-Yeon Kim; Hyeongjoo Oh; Soo-Il Kim; Woojin Na; Il-Jun Kang; Young-Hee Kang (Antioxidants, 2021)
Particulate matter (PM) is a mixture of solid and liquid air pollutant particles suspended in the air, varying in composition, size, and physical features. PM is the most harmful form of air pollution due to its ability to penetrate deep into the lungs and blood streams, causing diverse respiratory diseases. Aesculetin, a coumarin derivative present in the Sancho tree and chicory, is known to have antioxidant and anti-inflammatory effects in the vascular and immune system. However, its effect on PM-induced airway thickening and mucus hypersecretion is poorly understood. The current study examined whether naturally-occurring aesculetin inhibited airway thickening and mucus hypersecretion caused by urban PM10 (uPM10, particles less than 10 μm). Mice were orally administrated with 10 mg/kg aesculetin and exposed to 6 μg/mL uPM10 for 8 weeks. To further explore the mechanism(s) involved in inhibition of uPM10-induced mucus hypersecretion by aesculetin, bronchial epithelial BEAS-2B cells were treated with 1–20 µM aesculetin in the presence of 2 μg/mL uPM10. Oral administration of aesculetin attenuated collagen accumulation and mucus hypersecretion in the small airways inflamed by uPM10. In addition, aesculetin inhibited uPM10-evoked inflammation and oxidant production in lung tissues. Further, aesculetin accompanied the inhibition of induction of bronchial epithelial toll-like receptor 4 (TLR4) and epidermal growth factor receptor (EFGR) elevated by uPM10. The inhibition of TLR4 and EGFR accompanied bronchial mucus hypersecretion in the presence of uPM10. Oxidative stress was responsible for the epithelial induction of TLR4 and EGFR, which was disrupted by aesculetin. These results demonstrated that aesculetin ameliorated airway thickening and mucus hypersecretion by uPM10 inhalation by inhibiting pulmonary inflammation via oxidative stress-stimulated TLR4 and EGFR. Therefore, aesculetin may be a promising agent for treating airway mucosa-associated disorders elicited by urban coarse particulates.